Astronomijos ir meteorologijos jungtys Arato Reiškiniuose - Kardelis, Naglis (Literatūra, 2010)
The author of the article focuses on the connections between astronomy and meteorology in thePhaenomena of Aratus of Soli (fl. 276 BC). Firstly, the attention is drawn to such connections that are apparent in the structure of the poem which has two structural parts, the astronomical and the meteorological. It is shown that the astronomical part does not end abruptly, but merges gradually into the meteorological one. Such effect is achieved by way of methodical downward transition from the North pole and the upper sky, via the lower sky, to the atmosphere and then to the very surface of earth. Therefore, Aratus first of all describes the celestial phenomena as such, simply as marvels of the sky, without any reference to their prognostic (that is, meteorological) function. Then he speaks of them in relation to their prognostic function. After that the poet descends from the level of celestial phenomena to the level of earth’s atmosphere, that is, from astronomical to meteorological level, and focuses on meteorological phenomena proper, such as the rain, the storm, the wind, the snow, the rainbow, and so on, drawing attention to their prognostic function. Then the poet descends even lower, from the level of atmosphere to the level of earth’s surface, and describes various earthly phenomena, such as prognostically relevant physical and chemical properties of various common substances and strange behaviour of animals which also has significant prognostic value. In the process of the overall gradual descent from the North pole to the ground level, the poet, when it serves his artistic purpose, sometimes quickly and unexpectedly changes the scale from large to small (and vice versa), or altitude from high to low (and vice versa), or even speaks of various phenomena that simultaneously appear on different scale, large and small, and on different levels, astronomical and meteorological. Secondly, the author of the article analyses the connections between astronomical and meteorological levels that are apparent in the semantic shades of the words that Aratus uses to describe the astronomical and meteorological phenomena. One of the most interesting instances is the distinction between bright (aitherioenta) and dim (ēeroenta) celestial phenomena: such a distinction means that the difference between astronomy and meteorology is transferred to the realm of astronomy itself, astronomy proper, for among celestial bodies themselves some are described in terms of bright ethereal shining, while the others – in terms of dim “atmospheric“ glowing, as if the former fell into the category of the celestial phenomena that might be described as strictly and truly astronomical, while the latter – into the category of the celestial phenomena that might be accepted as astronomical only with some reservation, or even imagined as, so to speak, “meteorologically“ astronomical phenomena. The conclusion is drawn that various subtle connections between astronomical and meteorological levels of the poem show that both parts of Aratus’ Phaenomena, astronomical and meteorological, are organically interwoven and form a harmonious poetic whole which is reminiscent of the cosmic harmony itself.